Collaborative leadership practices of district-based education inspectors in supporting Teacher Professional Development in Lesotho - ‘Nei, ‘Makutloano Francina (University of the Free State, 2024)
The increasing global competition and focus on teacher quality and job satisfaction have led to teacher professional development (TPD) being regarded as crucial. Collaborative leadership practices are essential and are aimed at enhancing learner performance. In Lesotho, the Ministry of Education and Training officials do not seem to be creating diverse collaborative activities and various professional development platforms that keep teachers abreast with technological advancements, nor are their professional activities well-coordinated. However, the literature indicates that teacher professional development is more effective when it is sustained and collaborative. This study focused on the collaborative leadership practices of the district-based education inspectors in supporting teacher professional development in Lesotho. The study used the interpretive research paradigm. The research was informed by the two theories of David Chrislip and Carl Larson’s Collaborative Leadership Theory of 1994 and Ralph Fessler’s Eight-Eight Teacher Career Cycle Model 1995. Data was generated from four district-based education inspectors, four principals, four HODs, and six teachers from each of the four schools which were selected for this study. The study was carried out using a qualitative research approach and a multiple case study research design. The data generation methods used are semi-structured face-to-face interviews, focus groups, document analysis and the collage. This study used non-probability sampling technique in selecting the participants. Data was analysed using a thematic data analysis strategy, with the transcription, coding and interpretation of data in order to get the findings. The findings in this study revealed that the teacher professional development activities that were provided to the teachers were mainly workshops which were school-initiated while others were district-office- initiated. The study found that the district-based inspectors’ collaborative leadership practices were partially effective since there were some practices which were not happening as anticipated according to the principles of collaborative leadership. Such challenges still needed to be addressed in as far as the inspectors and their collaborative leadership roles were concerned. The study further highlighted the lack of resources, work overload, fear of inspectors’ intimidating approach, lack of feedback, lack of support for private schools, lack of exposure to a variety of teacher professional development activities, no tapping of available knowledge, lack of exposure to advanced technology as some of the factors affecting the collaborative leadership practices of the district-based inspectors. Therefore, the study recommended the establishment of structures that would provide TPD district-based education inspector support made of different stakeholders.

Die toenemende wêreldwye mededinging en fokus op onderwysersgehalte en werkstevredenheid het daartoe gelei dat die professionele ontwikkeling van onderwysers (Teacher Professional Development (TPD)) as uiters belangrik beskou word. Samewerkende leierskapspraktyke is noodsaaklik en het ten doel om leerderprestasie te verbeter. In Lesotho blyk dit dat amptenare van die Ministerie van Onderwys en Opleiding nie verskeie samewerkende aktiwiteite en professionele ontwikkelingsplatforms skep wat onderwysers op hoogte hou van tegnologiese vooruitgang nie en dat hul professionele aktiwiteite nie goed gekoördineer is nie. Die literatuur toon egter aan dat die professionele ontwikkeling van onderwysers meer effektief is wanneer dit volhoubaar en samewerkend is. Hierdie studie fokus op die samewerkende leierskapspraktyke van distriksgebaseerde onderwysinspekteurs in die ondersteuning van die professionele ontwikkeling van onderwysers in Lesotho. Die interpretatiewe navorsingsparadigma is gebruik en inligting is ingewin deur van twee teorieë gebruik te maak: David Chrislip en Carl Larson se teorie oor samewerkende leierskap (1994), en Ralph Fessler se model oor die onderwysersloopbaansiklus (1995). Data is gegenereer van vier distriksgebaseerde onderwysinspekteurs, vier skoolhoofde, vier departementshoofde en ses onderwysers van elk van die vier skole wat vir die studie gekies is. Die studie is uitgevoer deur ’n kwalitatiewe navorsingsbenadering en ’n meervoudige gevallestudie-navorsingsontwerp. Die metodes van datagenerering sluit semigestruktureerde aangesig-tot-aangesig onderhoude, fokusgroepe en ’n dokumentanalise in. In hierdie studie is ’n niewaarskynlikheidsteekproeftegniek gebruik om deelnemers te kies. Die data is ontleed deur middel van ’n tematiese ontledingsbenadering wat transkripsie, kodering en interpretasie insluit om die belangrikste bevindings te identifiseer. Die bevindings het getoon dat die professionele ontwikkelingsaktiwiteite vir onderwysers hoofsaaklik werkswinkels was waarvan die meeste deur skole geïnisieer is, terwyl sommige deur die distrikskantoor gereël is. Die studie het bevind dat die distriksgebaseerde inspekteurs se gesamentlike leierskapspraktyke slegs gedeeltelik effektief was. Sommige verwagte praktyke, soos uiteengesit in die beginsels van gesamentlike leierskap, het nie plaasgevind soos beplan nie wat aandui dat daar steeds aandag aan hierdie kwessies gegee moet word. Die studie het verskeie uitdagings uitgelig wat die doeltreffendheid van gesamentlike leierskap belemmer. Dit sluit ’n tekort aan hulpbronne, oorlading van werk, vrees vir inspekteurs se intimiderende benadering, gebrek aan terugvoer, onvoldoende ondersteuning vir privaat skole, beperkte blootstelling aan verskeie professionele ontwikkelingsaktiwiteite, onvoldoende benutting van beskikbare kennis en ’n gebrek aan toegang tot gevorderde tegnologie in. Gegrond op hierdie bevindings het die studie aanbeveel dat daar strukture geskep moet word wat ondersteuning bied aan distriksgebaseerde onderwysinspekteurs, bestaande uit verskeie belanghebbendes, om die impak en effektiwiteit van professionele ontwikkelingsinisiatiewe te verbeter.

Tlhodisano e ntseng e eketseha ya lefatshe le ho tsepamisa maikutlo ho boleng ba matitjhere, le kgotsofalo ya mosebetsi, di lebisitse ho ntshetsopele ya ditsebi tsa matitjhere (TPD) e nkwang e le ya bohlokwa. Mekgwa ya boetapele ya tshebedisano e bohlokwa mme e reretswe ho ntlafatsa tshebetso ya baithuti. Lesotho, basebeletsi ba Lekala la Thuto le Kwetliso ha ba bonahale ba theha mesebetsi e fapaneng ya tshebedisanommoho le diforomo tse fapaneng tsa ntshetsopele ya ditsebi tse bolokang matitjhere a le haufi le tswelopele ya mahlale, ebile mesebetsi ya bona ya botsebi ha e hokahane hantle. Leha ho le jwalo, dingodilweng di bontsha hore ntshetsopele ya ditsebi tsa matitjhere e atleha haholwanyane ha e etswa ka nako e telele le ka tshebedisanommoho. Diphuputso tsena di ile tsa lebisa tlhokomelo mekgweng ya boetapele ba tshebedisanommoho ya bahlahlobi ba thuto ba setereke ho tshehetsa ntshetsopele ya ditsebi tsa matitjhere Lesotho. Diphuputso tsena di sebedisitse mokgwa wa ho etsa dipatlisiso tse hlalosang. Patlisiso e ile ya tsebiswa ke dikgopolo tse pedi tsa David Chrislip le Carl Larson's Collaborative Leadership Theory ya 1994 le Ralph Fessler's Eight-Eight Teacher Career Cycle Model ya 1995. Dintlha kapa deitha e nkile ho bahlahlobi ba bane ba thuto ya setereke, batsamaisi ba bane, dihlooho tsa mafapha tse nne le matitjhere a tsheletseng, ho tswa ho e nngwe le e nngwe ya dikolo tse nne tse kgethilweng bakeng sa thuto ena. Diphuputso di ile tsa etswa ho sebediswa mokgwa wa ho etsa dipatlisiso tsa boleng le moralo wa dipatlisiso tsa dinyewe tse ngata. Mekgwa ya ho hlahisa boitsebiso e sebediswang ke dipuisano tsa sefahleho le sefahleho tse hlophisitsweng hantle, dihlopha tse tsepamisisang maikutlo, tlhahlobo ya ditokomane le kgobokanyo. Diphuputsong tsena ho sebedisitswe mokgwa wa ho kgetha batho bao e seng ba ka nnang ba ba teng ha ho kgethwa barupellwa. Deitha e ile ya manollwa ho sebediswa mokgwa wa ho hlahloba boitsebiso ka tsela ya dihlooho, ka ho ngola le ho hlalosa deitha e le hore ho fumanwe diphetho. Diphuputso tse entsweng diphuputsong tsena di bontshitse hore mesebetsi ya ntlafatso ya botsebi ya matitjhere e neng e fanwa ho matitjhere e ne e le dithupelo tse qadilweng ke sekolo ha tse ding di qadilwe ke ofisi ya setereke. Diphuputso di fumane hore mekgwa ya boetapele ba tshebedisano ya bahlahlobi ba setereke e ne e sebetsa ka mokgwa o itseng kaha ho ne ho na le mekgwa e meng e neng e sa etsahale jwalokaha ho ne ho lebeletswe ho latela melao ya motheo ya boetapele ba tshebedisano. Diphephetso tse jwalo di ne di ntse di hloka ho rarollwa ho ya fihla ho bahlahlobi le dikarolo tsa bona tsa boetapele ba tshebedisano. Diphuputso di boetse di totobatsa ho haella ha mehlodi, mosebetsi o mongata, tshabo ya bahlahlobi, mokgwa wa ho tshosa, ho haella ha maikutlo, ho haella ha tshehetso bakeng sa dikolo tsa poraefete, ho haella ha ho atlehisa mesebetsi e fapaneng ya ntlafatso ya matitjhere, ho se sebedise tsebo e fumanehang, ho haella ha ho sebedisa theknoloji e tswetseng pele e le tse ding tsa dintlha tse amang mekgwa ya boetapele ya tshebedisano ya bahlahlobi ba setereke. Ka lebaka leo, thuto e ile ya kgothaletsa ho thehwa ha mehaho e neng e tla fana ka tshehetso ho bahlahlobi ba thuto ba TPD ba thehilweng seterekeng ba entsweng ke ba amehang ba fapaneng.

Ukuncintisana okwandayo emhlabeni wonke kanye nokugxila eqophelweni lothisha kanye nokwaneliseka komsebenzi kuholele ekuthuthukisweni kochwepheshe bothisha (TPD) kubhekwe njengento ebalulekile. Izinqubo zobuholi ngokubambisana zibalulekile futhi kuhloswe ngazo ukuthuthukisa ukusebenza kwabafundi. E-Lesotho, izikhulu zoMnyango wezeMfundo Nokuqeqesha azibonakali zenza imisebenzi yokusebenzisana eyahlukahlukene kanye nezinkundla ezihlukahlukene zokuthuthukiswa kochwepheshe ezigcina othisha benolwazi ngentuthuko yezobuchwepheshe, futhi nemisebenzi yabo yobungcweti ayihlanganiswa kahle. Kodwa-ke, izincwadi zikhomba ukuthi ukuthuthukiswa kothisha kuphumelela kakhulu uma kuqhubeka futhi kubanjiswana. Lolu cwaningo lugxile ezenzweni zobuholi obubambisene zabahloli bezemfundo abazinze ezifundeni ekusekeleni ukuthuthukiswa kothisha eLesotho. Ucwaningo lusebenzise ipharadayimu yocwaningo lokuhumusha. Ucwaningo lwenziwe imibono emibili ye-David Chrislip kanye ne-Carl Larson's Collaborative Leadership Theory ka-1994 kanye ne-Eight-Eight Teacher Career Cycle Model ka-Ralph Fessler ka-1995. Imininingwane itholwe kubahloli abane bezemfundo ezifundeni, othishanhloko abane, abaphathi beminyango (HOD) abane, nothisha abayisithupha besikole ngasinye kwezine ezikhethelwe lolu cwaningo. Ucwaningo lwenziwe kusetshenziswa indlela yocwaningo olusezingeni eliphezulu kanye nomklamo wocwaningo lwezimo eziningi. Izindlela zokukhiqiza idatha ezisetshenziswayo yizingxoxo zobuso nobuso ezingahlelekile, amaqembu okugxilwe kuwo, ukuhlaziya amadokhumenti kanye nekholaji. Lolu cwaningo lusebenzise indlela yokuthatha amasampula okungewona amathuba ekukhetheni ababambiqhaza. Idatha yahlaziywa kusetshenziswa isu lokuhlaziya idatha yengqikithi, ngokulotshwa, ukubhala ngekhodi nokutolikwa kwedatha ukuze kutholwe okutholakele. Okutholwe kulolu cwaningo kuveze ukuthi imisebenzi yokuthuthukiswa kothisha eyanikezwa othisha ikakhulukazi kwakuyizinkundla zokucobelelana ngolwazi ezaqalwa izikole kanti ezinye zaqalwa ngamahhovisi esifunda. Ucwaningo luthole ukuthi izinqubo zobuholi obubambisene nabahloli beziyingi bezisebenza ngokwengxenye njengoba bekukhona imikhuba ebingenzeki njengoba bekulindelwe ngokwemigomo yobuholi obuhlangene. Lezi zinselelo bezisadinga ukubhekwana nazo mayelana nabahloli kanye neqhaza labo lobuholi obuhlangene. Lolu cwaningo luphinde lwagqamisa ukushoda kwezinsiza, umsebenzi omningi, ukwesaba ukwesabisa kwabahloli, ukungabi bikho kwempendulo, ukuntula ukusekelwa kwezikole ezizimele, ukuntula ukuchayeka ezinhlobonhlobo zemisebenzi yokuthuthukiswa kothisha, ukungathengi ulwazi olukhona, ukuntula ukuchayeka kobuchwepheshe obuphambili njengezinye zezinto ezithinta ubuholi obubambisene babahloli abazinze esifundeni. Ngakho-ke, ucwaningo luncome ukusungulwa kwezinhlaka ezizohlinzeka ngosizo lomhloli wezemfundo ozinze esifundeni se-TPD olwenziwa ababambiqhaza abahlukene.
Samewerkende leierskapspraktyke van distriksgebaseerde onderwysinspekteurs in die ondersteuning van die professionele ontwikkeling van onderwysers in Lesotho
Mekgwa ya boetapele ya tshebedisano ya bahlahlobi ba thuto ba setereke ho tshehetsa Ntshetsopele ya Mosebetsi wa Matitjhere Lesotho
Thesis (Ph.D.(Education Management and Leadership))--University of the Free State, 2024
Keywords: Collaborative leadership; Education leadership and management; Teacher professional development; Samewerkende leierskap; onderwysleierskap en -bestuur; professionele ontwikkeling van onderwysers; Boetapele bo kopanetsweng; Boetapele le tsamaiso ya thuto; Ntshetsopele ya botsebi ba matitjhere; Ubuholi obubambisene; ubuholi kanye nokuphatha kwezemfundo; Ukuthuthukiswa kochwepheshe bothisha